Implementasi Kebijakan Pengembangan Destinasi Pariwisata Budaya di Kabupaten Manggarai Barat - Hirodias, Eduardus; Hermawan, Hermawan; Amin, Fadilah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This research, which aims to analyze the process of implementing the policy of developing cultural tourism destinations in West Manggarai Regency, is reviewed through van Mater and Van Horn's approach: Basic measures and policy objectives, policy sources, interorganization communication and implementation activities, Characteristics of the implementing agencies, Social, Economy and Politics Conditions and disposition of Implementers, using qualitative research methods descriptive to identify some fundamentals related to the policy of developing cultural tourism destinations in West Manggarai. Based on the results of the research, the process of Implementing the Tourism Development Master Plan has been implemented but still leaves some fundamental problems, so that the implementation process does not work and leads to the achievement of the results that are the final goal of this policy, namely the attractiveness of cultural tourism which in terms of the quality of destinations and the quantity of tourists can become a tourist attraction and support the main tourist attraction of Komodo dragons, improving socio-economic life while introducing the culture and past history of the People of West Manggarai Regency.